2017
DOI: 10.1080/15384047.2017.1294290
|View full text |Cite
|
Sign up to set email alerts
|

The expression of asparaginyl endopeptidase promotes growth potential in epithelial ovarian cancer

Abstract: Epithelial ovarian cancer (EOC) is the most common and lethal cancer-related death among females in the world. Asparaginyl endopeptidase (AEP) is a member of C13 family peptidases and expressed in the extracellular matrix and tumor cells. The aim of this article is to explore the function of asparaginyl endopeptidase in epithelial ovarian cancer. The expression of AEP was examined in 20 EOC samples, 3 EOC metastasis samples, 6 fallopian tube metastasis samples, 4 peritoneum metastasis samples and 20 benign ova… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Asparagine endopeptidase (AEP), also known as legumain (LGMN), is a lysosomal cysteine proteinase belonging to the C13 family peptidases [ 30 ]. AEP is highly expressed and correlates with poor prognosis and advanced clinical stage in various solid tumors including rectal cancer [ 31 ], breast cancer [ 32 , 33 ], epithelial ovary cancer [ 34 ] and gastric cancer [ 35 ]. Our previous work showed that, after being cleaved at N311, wild-type p53 can be inactivated by AEP, leading to the loss of the p53 tumor suppressor function in GBM [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…Asparagine endopeptidase (AEP), also known as legumain (LGMN), is a lysosomal cysteine proteinase belonging to the C13 family peptidases [ 30 ]. AEP is highly expressed and correlates with poor prognosis and advanced clinical stage in various solid tumors including rectal cancer [ 31 ], breast cancer [ 32 , 33 ], epithelial ovary cancer [ 34 ] and gastric cancer [ 35 ]. Our previous work showed that, after being cleaved at N311, wild-type p53 can be inactivated by AEP, leading to the loss of the p53 tumor suppressor function in GBM [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have demonstrated that ion channels play an important role in tumorigenesis and progression, such as inducing neo-angiogenesis [65], apoptosis resistance [66], proliferative potential [67] as well as cell migration and invasiveness [68, 69]. In terms of endopeptidase activity, Zhu et al [70]. demonstrated that asparaginyl endopeptidase (AEP) was highly expressed in tissues and ascites of patients with epithelial ovarian cancer and promoted tumor growth and progression both in vivo and in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…However, it also occurs extracellularly and even translocates to the cytosol and the nucleus. LGMN has also been reported to be associated with the development of a variety of tumor types, including breast cancer, gastric carcinoma, ovarian and colorectal cancer, and it may even serve as a biomarker for such tumors (31)(32)(33)(34). Furthermore, LGMN was indicated to promote the proliferation and invasiveness of prostate cancer cells via the PI3K/AKT signaling pathway (35).…”
Section: Discussionmentioning
confidence: 99%